Surface water and groundwater characteristics in the wetlands of the Ajó River (Argentina) - Carol, E. (2012)
Intertidal wetlands are complex hydrological environments in which surface water and groundwater interact periodically with tidal flows. This work analyzes how the tidal flow determines the hydrodynamics and salinity of surface water and groundwater at different depths in the intertidal wetland located in the marsh of the Ajó River. Water level and salinity measurements were obtained from the Ajó River, the channels discharging into the river and the phreatic aquifer. The results in the natural marsh indicate the presence of saline stratification and that the surface water–groundwater relationship varies with the tide. At low tide, the water table discharges into the surface watercourses, and when the high tide rises above the regional groundwater discharge level, the tidal flow contributes to the water table, which causes an increase in salinity in surface water and groundwater. When the high tide does not rise above the discharge level, the tidal flow only enters the groundwater at the mouth section and the salinity of the surface water and groundwater decreases from low tide to high tide. In the marsh areas excluded from the tidal cycle due to the presence of floodgates, the water table always discharges into the canals, and in the surface water and groundwater there is no presence of saline stratification. The results obtained make it possible to generate a conceptual model of hydrological behaviour which shows the hydrodynamic and hydrochemical complexity of intertidal wetlands.